Implementation of a Web-Based Accounting Information System for Management of Consumable Goods Inventory Case Study: Banjarbaru City Regional Revenue Service Unit - Nadia Puteri Utami; Muhammad Bahit; Tiara Regita Cahyani (International Forum of Researchers and Lecturers, 2023)
An Accounting Information System (AIS) for inventory of consumable goods is important in inventory management, transaction recording and financial reporting. A consumables inventory AIS helps in monitoring stock, calculating inventory costs, and ensuring proper accountability within the company. The problems that occur in the inventory recording system for consumable goods, namely that the recording that is still being carried out is not in accordance with applicable accounting so that the physical entry and exit of goods cannot be known periodically and there is no SIA for the Banjarbaru City Regional Revenue Service Unit. This research aims to create a Web-based SIA for inventory of consumables at the Banjarbaru City Regional Revenue Service Unit. This research method uses the case study method. The results of the research found that web-based AIS for managing supplies of consumables at the Banjarbaru City Regional Revenue Service Unit runs more effectively and efficiently. Keywords: Accounting Information Systems, Consumables, Accounting Application Programs.